Haar Cascade Classifier and Adaboost Algorithm for Face Detection with the Viola-Jones Method - Nidom, Mohammad Saichu (Department of Informatics, Faculty of Da'wah, UIN Saizu Purwokerto, 2025)
Face detection is a significant challenge in image processing and computer vision, with broad security, identity recognition, and human-computer interaction applications. This study explores the effectiveness of the Haar Cascade Classifier method optimized with Adaboost to improve the accuracy and efficiency of face detection in various head covering conditions. In this experiment, two approaches were compared: using the Haar Cascade Classifier independently and in combination with Adaboost, with evaluation based on metrics such as accuracy, precision, sensitivity, and F1-Score. The results showed that the Adaboost combination significantly improved detection accuracy, with the